Crystallization of Potassium Dihydrogen Phosphate Considering Particle Size Evolution - Tam Minh Le,; Phuong Bui Thi Thanh,; Tuyen Kha Chan, (Journal of Technical Education Science, 2025)
Potassium dihydrogen phosphate (KDP) is widely utilized in food additives, laser technology, and multi-nutrient fertilizers. Besides the purity, particle size distribution (PSD) of KDP is critical quality parameter, which is the primary focus in this study. For this purpose, a systematic study was carried out. KDP crystals were synthesized through a crystallization process employing various operation modes. The evolution of crystal size over time was monitored using two distinct techniques, including real-time online monitoring via laser measurement and offline analysis through microscopic analysis. The crystal growth dynamics were found to be influenced by the degree of supercooling and the anti-solvent employed. Crystals obtained through natural cooling versus anti-solvent technique exhibited that nucleation and crystal growth are strongly dependent on fluctuations in supersaturation levels. Chemical composition analysis of the optimized products revealed that the KDP crystals achieved a purity greater than 99%, confirming that the crystallization process was efficient, with minimal incorporation of impurities into the crystal structure, thereby ensuring the product's quality.